2019
DOI: 10.4018/ijpada.2019100101
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Local Governance and E-Services in Qatar

Abstract: Properly implemented, e-government enables improved government efficiency and greater engagement with citizens. The State of Qatar has implemented many e-government initiatives but little has been done to investigate their progress. This study aims to bridge the knowledge gap by shedding the light on a specific e-government initiative: the Baladiya application system, the electronic service for municipalities. It uses qualitative data from semi-structured interviews conducted with the director of customer serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
(1 reference statement)
0
6
0
Order By: Relevance
“…First, the link between vision, strategy, action plans, initiative goals and outcomes, although Qatar itself would benefit if strengthen in this further domestically as indirectly proposed by Benmansour et. al [8]. This had a positive effect in overcoming some of the challenges discussed by Weerakkody & Al-Shafi [51] in Qatar and increase the country's global performance on the ESCWA, UNDESA and World Bank benchmarks [14,17,18,54].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…First, the link between vision, strategy, action plans, initiative goals and outcomes, although Qatar itself would benefit if strengthen in this further domestically as indirectly proposed by Benmansour et. al [8]. This had a positive effect in overcoming some of the challenges discussed by Weerakkody & Al-Shafi [51] in Qatar and increase the country's global performance on the ESCWA, UNDESA and World Bank benchmarks [14,17,18,54].…”
Section: Discussionmentioning
confidence: 99%
“…The Qatari approach is to have a strategic KPIs, but the linkage to operational KPIs is not clear and need to be aligned with initiatives and projects KPIs -point also made by Benmansour et. al [8] who found that little have been done to measure the impact of ICT investments when explore local governance and eServices in Qatar. This supports the conclusions of Klievink et.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations